MODEL PEMBELAJARAN DICK AND CARREY DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA - Aji, Wisnu Nugroho (Kajian Linguistik dan Sastra, 2016)
The quality of process and learning outcome always gathers side by sideand proportional. The qualified learning process will produce the qualifiedlearning outcome. The indicator of learning process is emerging by using correctlearning model to support the learning outcome. Dick and Carrey leaning modelis one of those models. The use of Dick and Carey model which is gathered withthe scientific approach of curriculum 2013 is proven empirically in supportingthe learning outcome of Indonesian language and literature. This research aimsto describe the implication of dick and carrey learning model on Indonesianlanguage and literature learning process. The result shows that this model is aperfect match for the subject because the model is referring to the general stagesin learning system development. Moreover, dick and carrey model has ten stepson systematical learning process that makes it appropriate for the implicationsof 2013 curriculum.